A comparative Study on Chemical Composition and Antimicrobial Activity of Essential Oils from Tanacetum parthenium (L.) Schultz. Bip. and Tanacetum punctatum (Desr.) Grierson. Leaves from Iran. Issue 4 (4th July 2017) - Shafaghat, Ali; Ghorban-Dadras, Orkideh; Mohammadhosseini, Majid; Akhavan, Maliheh; Shafaghatlonbar, Masoud; Panahi, Akram
Abstract: The essential oils of Tanacetum parthenium (L.) Schultz. Bip. and Tanacetum punctatum (Desr.) Grierson. leaves were obtained by hydrodistillation and analysed by GC and GC-MS. The oil yields (v/w) on moisture free basis of T. parthenium and T. punctatum leaves were 0.8 % and 0.2 %, respectively. The essential oil of T. parthenium and T. punctatum were characterized by a higher amount of camphor (53.8 % and 45. 5%), trans -β-farnesene (8.3 % and 7.4 %), camphene (6.9 % and 6.2 %), β-caryophyllene (5.9 % and 9.7 %) and chrysanthenone (3.3 % and 4.1 %), respectively. Bornyl acetate (3.1 %), 4-hydroxy-benzenepropanoic acid (3. 7%) and borneol (2.9 %) among the 24 components of the total oil from T. parthenium sample were detected. Thirty two components were characterized representing 96.9 % of total constituents detected in the oil of T. punctatum . In this oil, 4-hydroxy-benzenepropanoic acid (2.2 %) and borneol (2.1 %) were also the predominating compounds. The antimicrobial activity of both samples was determined against seven bacteria and three fungi. The bioassay showed that the oil exhibited a good antimicrobial activity.